2018
DOI: 10.1002/naaq.10057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Carbohydrate/Lipid Ratios on Growth, Feed Utilization, Hematology Parameters, and Intestinal Digestive Enzyme Activities of Juvenile Hybrid Grouper (Brown‐Marbled Grouper Epinephelus fuscoguttatus ♀ × Giant Grouper E. lanceolatus ♂)

Abstract: An 8‐week growth trial was conducted to investigate the effects of dietary carbohydrate (CHO)/lipid (L) ratios on growth, feed utilization, hematology parameters, and intestinal digestive enzyme activities of juvenile hybrid grouper (Brown‐marbled Grouper Epinephelus fuscoguttatus ♀ × Giant Grouper E. lanceolatus ♂). Seven isoproteic (53.5% dietary crude protein) and isoenergetic (3.6 kcal/g dry matter) experimental diets were formulated containing various CHO/L ratios: 0.03 (0.5% CHO/16% L); 0.36 (5% CHO/14% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…There were no significant differences in moisture, ash, and crude protein content between all treatment groups. In contrast, crude lipid decreased significantly with the increase in dietary CHO:L ratio, which was consistent with previous reported on large yellow croaker [ 28 ], hybrid Clarias catfish ( Clarias macrocephalus × C. gariepinus ) [ 36 ], and juvenile hybrid grouper [ 19 ]. When nutritional requirements are fulfilled, the appropriate lipid content in the diet is about 10% for hybrid grouper [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were no significant differences in moisture, ash, and crude protein content between all treatment groups. In contrast, crude lipid decreased significantly with the increase in dietary CHO:L ratio, which was consistent with previous reported on large yellow croaker [ 28 ], hybrid Clarias catfish ( Clarias macrocephalus × C. gariepinus ) [ 36 ], and juvenile hybrid grouper [ 19 ]. When nutritional requirements are fulfilled, the appropriate lipid content in the diet is about 10% for hybrid grouper [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…In order to maximize profits, diets are often formulated to contain high levels of CHO:L ratio to reduce feed costs. Although the optimal glycolipid ratio requirements at the juvenile stage of grouper have been studied [ 18 , 19 , 20 ], there is little research on the addition of carbohydrase based on different glycolipid ratios. With this in mind, the purpose of this study was to assess the influence of carbohydrase supplementation on growth performance, carbohydrate metabolic enzyme and glut2 gene expression in the Hybrid Grouper-fed diets with different CHO:L ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches include the use of modified starches that provide physical structure to compounded feed without resulting in excess liver glycogen deposition. 56 When compared on a balanced digestible energy basis, lipid is preferred over carbohydrate as an energy source for TGGG, with linearly decreased growth when lipid energy is replaced by starch energy 49,57 or starch increased at constant lipid levels. 49 Interestingly, the former finding was largely attributed to a lack of lipid rather than any negative attributes of excessive carbohydrates, whereas the latter study indicated that 8% starch is optimal and higher levels led to decreased growth.…”
Section: Energ E Tic S; Fat C Arbohydr Ate S and Protein A S Energy Source Smentioning
confidence: 99%
“…33-35 c Lipid used to balance constant energy in feeds for different fish size, within the appropriate range reported. 38,39,49 d While apparently desirable to limit starch to this level, 49,57 Tryptophan Required-unknown quantitative requirement due to lack of data but are also required for optimal growth and health. 116,117 Both of these vitamins are present in significant quantities in fish oil, but at vastly variable concentrations, 118 and therefore, it is challenging to derive a likely contribution from raw materials in order to specify a premix addition.…”
Section: Nutrient Requirements For Formul Ated Feedsmentioning
confidence: 99%
See 1 more Smart Citation